Theorizing the Halal Brand Association toward the Participation in Family Takaful Product: An Extended Theory of Planned Behaviour (Journal of Entrepreneurship and Business, 2025)
This study examines the pivotal role of halal brand association (HBA) in influencing consumer participation in family takaful products through the Theory of Planned Behaviour (TPB). The research conceptualizes HBA as a critical variable impacting key TPB predictors—attitude, subjective norms, and perceived behavioral control—leading to increased participation in family takaful products. A qualitative approach systematically reviewed literature from reputable academic databases to develop a theoretical framework. The findings reveal that HBA enhances consumer attitudes, aligns with social expectations, and strengthens perceived behavioral control. Academically, this study contributes to the limited research on HBA in the takaful industry, providing new insights into consumer behavior in Islamic finance. Practically, it offers strategic guidance for Islamic financial institutions to leverage halal branding as a competitive advantage. By aligning financial products with Islamic ethical principles, this research underscores the dual importance of religious compliance and social responsibility in fostering consumer engagement and loyalty.
Keywords: Array; Array; Array